Women’s Politicians in 2014 Political Parties: Descriptive versus Substantive Representations. - Nuri Soeseno (Jurnal Perempuan, 2014)
Women’s representation in parties and legislative institution is closely related to Indonesian’s party typology as office seekers. It charted descriptive mandate to fulfill 30% quote of women’s representation in General Election 2014—not necessary representing women’s critical agenda. The phenomena of female legislators working previously as celebrities, actress, singers, or coming from political dynasty is the consequence of office seekers parties. It does not then guarantee the promotion, empowerment and protection of women’s critical issues in societies as they are not representing women in general substantively. It is necessary to create female critical actors coming to office in political parties to succeed feminist agenda.